Did the Fertilizer Cartel Cause the Food Crisis? - Hinnerk Gnutzmann; Piotr Spiewanowski (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Food commodity prices escalated during the 2007/2008 food crisis, and have scarcely fallen since. We show that high fertilizer prices, driven by the formation of an international export cartel as well as high energy prices, explains the majority of the recent price spikes. In particular, we estimate the pure fertilizer cartel effect explains up to 50% of crisis food price increases. While population growth, biofuels, high energy prices and financial speculation doubtlessly put stress on food markets, our results help to understand the severity and sudden emergence of the crisis and suggest avenues to prevent its repetition.
Keywords: F10; L40; Q02; 330